UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA KEMAMPUAN MEMBACA AL-QUR'AN SISWA DI MA MUHAMMADIYAH KABILAH KABUPATEN BONE BOLANGO - Nurul Albar Nanggo; Hasyim M. Wantu; Eka Apristian Pantu; Rendy S. Sambara (CV. Lafadz Jaya, 2026)
The ability to read the Qur'an is a fundamental competency that every Muslim student is expected to develop. Islamic Religious Education teachers play a central role in fostering this competency through learning strategies that accommodate students' diverse abilities. This study aims to describe the efforts of Islamic Religious Education teachers in improving students' Qur'anic reading skills, identify the supporting and inhibiting factors, and analyze the solutions implemented at MA Muhammadiyah Kabilah, Bone Bolango Regency. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that teachers improve students' Qur'anic reading skills through daily reading habituation, the application of the Iqra' and Talaqqi methods, the use of instructional media, and periodic reading assessments. The success of the program is supported by teacher competence, institutional support, and parental involvement, while the main obstacles include students' varying initial abilities, limited instructional time, low learning motivation, and insufficient practice at home. These challenges are addressed through individualized guidance, supplementary learning sessions, motivational reinforcement, and collaboration with parents.